The Beka-Ocizla Cave System - Knez, M (Springer, 2015)
A proposed railway on the 5th European Railway Corridor (Venice-Kiev) between the northern Adriatic ports of Koper (Slovenia) and Trieste (Italy) and the interior of Slovenia required extensive karstological studies and planning. This book contains the knowledge gained from these studies as well as further information on the regional karst surface and underground, the karst hydrogeology and the specific caves of the Beka-Ocizla cave system.